IMPLEMENTASI PROGRAM LITERASI HARIAN 15 MENIT DAN DAMPAKNYA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS II SD - Rohyana, Hadi; Fathoni, Isna Muhammad; Sri Legowo, Yogi Ageng (Faculty of Teacher Training and Education of Undaris, 2025)
This study evaluates the effectiveness of the “15-Minute Daily Literacy Program” (PLH-15) in improving reading-comprehension skills among second-grade elementary students. A quasi-experimental, single-group pre-test–post-test design was implemented at SD Bani Saleh, Bekasi. Thirty-two pupils were selected through purposive sampling. For eight weeks, participants engaged in 15-minute silent-reading sessions each morning before lessons, using grade-appropriate materials encompassing fiction, nonfiction, and illustrated informational texts. Data were gathered via the national-curriculum reading-comprehension test, reading-interest observation sheets, and brief teacher interviews. Statistical analysis revealed a significant rise in mean comprehension scores from 58.4 to 76.1 (p < 0.01), with an effect size of Cohen’s d = 0.98, indicating a strong impact. Observations recorded a 42 % increase in library book loans and greater participation in classroom reading discussions. Teacher interviews corroborated quantitative findings, noting heightened enthusiasm and confidence when students answered text-based questions. The study recommends institutionalizing the PLH-15 routine, expanding leveled reading collections, and training teachers in literacy strategies. These results underscore that a simple yet consistent intervention can strengthen early-literacy foundations and support the attainment of Indonesia’s “Profil Pelajar Pancasila” competencies at the primary-school level.Keywords: Daily Literacy, Reading Comprehension, Second-Grade Students, Merdeka Curriculum